Combination of bioprotective cultures with EDTA to reduce Escherichia coli O157:H7 in frozen ground-beef patties - Castellano, Patricia Haydee (2011)
The effectiveness of bacteriocin-producing Lactobacillus curvatus CRL705 and Lactococcus lactis CRL1109 in combination with Na2EDTA on frozen ground-beef patties contaminated with Escherichia coli O157:H7, was investigated under temperature abuse conditions (5 C during 9 days). The presence of the bioprotective cultures (ca. 107 CFU/g) and chelator (48 mM) resulted in one log CFU/g reduction for E. coliLactobacillus curvatus CRL705 and Lactococcus lactis CRL1109 in combination with Na2EDTA on frozen ground-beef patties contaminated with Escherichia coli O157:H7, was investigated under temperature abuse conditions (5 C during 9 days). The presence of the bioprotective cultures (ca. 107 CFU/g) and chelator (48 mM) resulted in one log CFU/g reduction for E. coli2EDTA on frozen ground-beef patties contaminated with Escherichia coli O157:H7, was investigated under temperature abuse conditions (5 C during 9 days). The presence of the bioprotective cultures (ca. 107 CFU/g) and chelator (48 mM) resulted in one log CFU/g reduction for E. coliC during 9 days). The presence of the bioprotective cultures (ca. 107 CFU/g) and chelator (48 mM) resulted in one log CFU/g reduction for E. coli7 CFU/g) and chelator (48 mM) resulted in one log CFU/g reduction for E. coli strain, compared to the control on day 0. Similarly, a significant decline for indigenous coliforms in ground-beef patties was also observed in the presence of bacteriocinogenic strains and chelator. However, in the absence of Na2EDTA, neither E. coli nor coliforms were inhibited by the bioprotective cultures, the pathogen reaching similar counts than control samples (5.22 and 3.60 log CFU/g, respectively) at 9 days. When the growth of bacteriocinogenic strains on patties was evaluated, they were able to increase their population producing bacteriocins after 48 h up to the end of incubation period while a near neutral pH in the presence of Na2EDTA was detected. Non substantial effect on of ground-beef patties color was produced in the presence of bioprotective cultures, while a darker color developed in those added with the chelator. The simultaneous treatment with bioprotective cultures and Na2EDTA may be of value for the control of E. coli O157:H7 in temperature abused ground-beef patties.ficant decline for indigenous coliforms in ground-beef patties was also observed in the presence of bacteriocinogenic strains and chelator. However, in the absence of Na2EDTA, neither E. coli nor coliforms were inhibited by the bioprotective cultures, the pathogen reaching similar counts than control samples (5.22 and 3.60 log CFU/g, respectively) at 9 days. When the growth of bacteriocinogenic strains on patties was evaluated, they were able to increase their population producing bacteriocins after 48 h up to the end of incubation period while a near neutral pH in the presence of Na2EDTA was detected. Non substantial effect on of ground-beef patties color was produced in the presence of bioprotective cultures, while a darker color developed in those added with the chelator. The simultaneous treatment with bioprotective cultures and Na2EDTA may be of value for the control of E. coli O157:H7 in temperature abused ground-beef patties.2EDTA, neither E. coli nor coliforms were inhibited by the bioprotective cultures, the pathogen reaching similar counts than control samples (5.22 and 3.60 log CFU/g, respectively) at 9 days. When the growth of bacteriocinogenic strains on patties was evaluated, they were able to increase their population producing bacteriocins after 48 h up to the end of incubation period while a near neutral pH in the presence of Na2EDTA was detected. Non substantial effect on of ground-beef patties color was produced in the presence of bioprotective cultures, while a darker color developed in those added with the chelator. The simultaneous treatment with bioprotective cultures and Na2EDTA may be of value for the control of E. coli O157:H7 in temperature abused ground-beef patties.2EDTA was detected. Non substantial effect on of ground-beef patties color was produced in the presence of bioprotective cultures, while a darker color developed in those added with the chelator. The simultaneous treatment with bioprotective cultures and Na2EDTA may be of value for the control of E. coli O157:H7 in temperature abused ground-beef patties.2EDTA may be of value for the control of E. coli O157:H7 in temperature abused ground-beef patties.E. coli O157:H7 in temperature abused ground-beef patties.